Peningkatan Kemampuan Pemecahan Masalah Dalam Materi Sistem Persamaan Linear Dua Variabel Menggunakan Langkah - Langkah Polya(PTK Bagi Siswa Kelas X Tata Busana A Semester Ganjil SMK Negeri 9 Surakarta Tahun 2015/2016) - Nur Hargana, Arisma; , Idris Harta, M.A,M.Pd (2016)
Main of this research was to improve the ability of tudents with problem-solving steps in Polya learning systems of linear equations two variables. This research approach was qualitative research with action research design class (CAR). Research on the subject of research is the whole grade X Tata Busana A SMK Negeri Surakarta 9 amounted to 32 students. The technique of collecting data through observation, field notes, documentation and tests. Data analysis technique used is the method by which consist of the reduction of flow data, data presentation, and data verification. The results showed that with steps can mprove the Polya problem solving students. It is seen from the indicator of mathematical problem solving of students includes 1) students in identify asked and seen unsure, before action (31,25%) and at the end of action (93,375%). 2) students in applying strategy, before action (25.00%) and at the end of action (93,375%). 3) students in plaining/ interpret result, before the Act (28.75%) and at the end of action (87,50%). Conclusion of this research is that with the measures may enhance the ability of solving Polya problem students in material systems of linear quations two variables.